Pengaruh Kedisiplinan dan Lingkungan Kerja terhadap Kinerja Pegawai pada Kelurahan PGS Cimanggis - Aldaina, Adien; Siska, Elmira; Indra, Natal (Jurnal Manajemen Riset Inovasi, 2023)
This study aims to determine how much influence employee discipline and work environment have on employee performance in the PGS Cimanggis Village. The research method is a quantitative approach using non-probability sampling data collection techniques. The number of samples taken using the slovin formula is as many as 52 respondents. Primary data was collected using questionnaires in Likert scale units. Data processing uses SPSS 26 software for instrument testing, classical assumption testing, multiple linear regression analysis, hypothesis testing, and the coefficient of determination. The results of the study show that work discipline partially has a positive and significant relationship to employee performance. The work environment also has a positive and significant relationship to employee performance. Then through simultaneous testing of the two variables of work discipline and the work environment have a positive and significant relationship to employee performance